Penerapan Metode FMEA Dan AHP Dalam Penentuan Prioritas Mitigasi Risiko Produksi Puding Buah Pada Umkm Salad Buah Rahma (SBR) - Dzurotun Nafisah; Sekar Ayu Wulandari; Dini Nafisatul Mutmainah; Cindiah Syahnaz S (Kampus Akademik Publiser, 2026)
This study aimed to identify production risks and determine mitigation strategy priorities for fruit pudding production at Salad Buah Rahma (SBR) MSME using the Failure Mode and Effect Analysis (FMEA) and Analytical Hierarchy Process (AHP) methods. A descriptive mixed-methods approach was employed, combining qualitative and quantitative techniques. Qualitative data were obtained through observations, interviews, and documentation to identify potential production risks, while quantitative data were collected using FMEA assessment sheets and AHP questionnaires. Respondents were selected through purposive sampling and consisted of the business owner, production supervisor, production workers, academics, and similar business practitioners with knowledge of production processes and risk management. The FMEA method was applied to evaluate each potential failure based on Severity (S), Occurrence (O), and Detection (D), producing a Risk Priority Number (RPN) for each identified risk. The results identified three priority risks: incomplete production Standard Operating Procedures (SOP) with an RPN of 512, storage facility failure with an RPN of 441, and incorrect ingredient measurement with an RPN of 392. These risks were subsequently used as criteria in the AHP analysis to determine the priority of mitigation strategies. The AHP results indicated that developing and implementing detailed SOPs was the highest-priority strategy with a global weight of 0.3279 (32.79%), followed by production process improvement at 0.2517 (25.17%), storage facility improvement at 0.2167 (21.67%), and employee training at 0.2037 (20.37%). The findings indicate that integrating FMEA and AHP provides a systematic approach for identifying priority production risks and selecting effective mitigation strategies. The recommended strategies are expected to improve production consistency, maintain product quality, reduce production failures, and strengthen risk management practices, thereby supporting the operational sustainability and competitiveness of food-based MSMEs.